AB0259 THE RELATIONSHIP BETWEEN MICROVASCULAR DAMAGE AND DISEASE ACTIVITY IN PATIENT WITH RHEUMATOID ARTHRITIS – ASSESSMENT BY VIDEOCAPILAROSCOPY. (2nd June 2020) - Parvu, M.; Cozos, A.; Biro, A. I.; Popoviciu, H. V.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by erosive synovitis (causing severe joint damage) and systemic damage. Rheumatoid vasculitis (RV) is an extra-articular manifestation of rare but serious rheumatoid disease that involves the damage of small and medium sized vessels. Objectives: The purpose of the study was to evaluate the incidence of damages occurred on cutaneous level in patients diagnosed with RA and to detect capillaroscopic microangiopathy changes in the activity of rheumatoid disease. Methods: 101 patients were included in the study, all were diagnosed with RA according to the ACR/EULAR 2010 criteria. RV diagnosis was based on the clinical examination. The capillaroscopic evaluation was performed with a 3.0 VideoCap device at a 200x magnification (200x magnification contact lenses). Capillaroscopic examination was performed on fingers II-V of both hands, being considered pathological if the capillaroscopic changes are present in at least two fingers. The activity of disease was calculated using DAS 28 ESR score. Results: 18% of examined patients was male and 82% female, with the mean age of 56, 2years±10.16SD, and the mean duration of the disease in years of illness was 8.65±5.31SD. 3 patients had periungual vasculitis with cutaneous ulceration and gangrene, 12 patients had palpable purpura. 29% of the patients had vasospastic skin changes. The activity score of RA was associated with the capillaroscopic changes in peripheral microangiopathy p-0.037. Capillaries images were heterogenous in aspects and distribution, tortuous capillaries, microhemorrhages, giant/dilated capillaries, avascular areas were observed. Conclusion: Vascular microangiopathy evidenced by capillaroscopic examination is present in patients with cutaneous vasculitis having a medium, severe activity of rheumatoid diseases. References: [1]Cutolo M, Paolino S, Smith V. Nailfold capillaroscopy in rheumatology: ready for daily use but care in terminology. Clinical Rheumatology 2019; 38:2293-2297 http://doi.org/10/s10067-019-04716-w [2]Lambova N, Müller-Ladner U. Capillaroscopic pattern in inflammatory arthritis. Microvascular Research 2012; 83:318-322 Dilated, giant capillaries, microhemorrhage bleedings, avascular area Reduced blood flow (observed in dynamics) Disclosure of Interests: Mirela Parvu Speakers bureau: Not for this subject, theme, Anca Cozos Speakers bureau: Not for this subject, theme, Anna-Iuliana Biro Speakers bureau: Not for this subject, theme, Horatiu Valeriu Popoviciu Speakers bureau: Not for this subject, theme